PROTOTIPE MONITORING SUHU RUANGAN DAN DETEKTOR GAS BOCOR BERBASIS APLIKASI BLYNK - Gede Sastra Utara; N.M.A.E.D. Wirastuti; Widyadi Setiawan (Program Studi Teknik Elektro UNUD, 2020)
In everyday life we often use the name LPG gas even as basic needs. However, in its use itcan pose a threat because of a large enough LPG gas. The occurrence of gas leaks when there areno people around the leak is very difficult to detect especially lethal substances contained in LPG gas.To reduce fires caused by LPG gas leaks, a monitoring system is needed to monitor if a leakoccurs.The prototype method for monitoring room temperature and gas detector leak using theArduino uno 328 mitrocontroller by connecting ESP8266 for wifi connection. ESP8266 will send datawhen the MQ2 sensor reads a gas leak, as well as changes in room temperature that is read by theDHT11 sensor by sending the sensor reading data to Arduino ATmega 328 first to be processed intothe response data of the device and data that will be displayed on the blynk application.The result ofthe achievement of this research is that the measurement of leaky gas using the MQ2 sensor canalready be displayed using the avo meter by obtaining the voltage results. Real gas leakagemeasurements in the field can be displayed on mobile phones through the Blynk application media.The leaked gas graph can be displayed in the Blynk application by getting the minimum andmaximum results. The ESP8266 module must be located in an area or location that has a Wi-finetwork in order to send notifications properly according to the instructions on Arduino ATmega 328.